IoThinking: A Design Thinking technique to support the design of IoT systems - Souza, Eriky; Façanha, Carla; Rocha, Conceição; Barbosa, Max; Souza, Sabrina; Gomes, Genildo; Lauschner, Tanara; Gadelha, Bruno; Conte, Tayana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Context: Designing IoT-based systems requires considering their specific characteristics like hardware devices, integration with other software, and different actors. But there is a lack of specific techniques to support defining essential elements in IoT systems development. Objective: This paper presents IoThinking, a Design Thinking technique that aims to support developers designing IoT systems. Method: We developed IoThinking based on research about IoT systems characteristics and Design Thinking techniques. Then we conducted a feasibility study to investigate if the technique supports the identification of relevant factors in developing IoT systems. We also analyzed data referring to users’ perceptions about the ease of use and usefulness of IoThinking during the design of an IoT system and captured feedback. Results: Our preliminary results present that IoThinking supported participants in identifying factors in an IoT system. We also received feedback about the perceived usefulness, ease of use, and suggestions that contributed to IoThinking evolution. Considering the received feedback, an updated version of the technique was also developed. Conclusion: Our preliminary result point out its feasibility in describing the relevant factors of an IoT system.